Dice and gods on the Silk Road : Chinese Buddhist dice divination in transcultural context - Dotson, Brandon, 1978-; Cook, Constance A.; Lu, Zhao (Professor of China studies) (Prognostication in History Ser., 2021)
"What do dice and gods have in common? What is the relationship between dice divination and dice gambling? This interdisciplinary collaboration situates the tenth-century Chinese Buddhist "Divination of Maheśvara" within a deep Chinese backstory of divination with dice and numbers going back to at least the 4th century BCE. Simultaneously, the authors track this specific method of dice divination across the Silk Road and into ancient India through a detailed study of the material culture, poetics, and ritual processes of dice divination in Chinese, Tibetan, and Indian contexts. The result is an extended meditation on the unpredictable movements of gods, dice, divination books, and divination users across the various languages, cultures, and religions of the Silk Road"--